2015
DOI: 10.1111/apa.13007
|View full text |Cite
|
Sign up to set email alerts
|

Family Nurture Intervention in preterm infants alters frontal cortical functional connectivity assessed by EEG coherence

Abstract: Aim: To assess the impact of Family Nurture Intervention (FNI) on cortical function in preterm infants at term age.Methods: Family Nurture Intervention is a NICU-based intervention designed to establish emotional connection between mothers and preterm infants. Infants born at 26-34 weeks postmenstrual age (PMA) were divided into two groups, standard care (SC, N = 49) and FNI (FNI, N = 56). Infants had EEG recordings of~one hour duration with 124 lead nets between 37 and 44 weeks PMA. Coherence was measured bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 30 publications
4
45
0
Order By: Relevance
“…FNI was designed to help reestablish the emotional connection (Hane et al, ) between mothers and their infants that was disrupted by the preterm delivery and the experiences of mother and infant within the NICU. Findings thus far have shown that FNI led to greater maternal sensitivity during routine caregiving behavioral interactions (Hane et al, ), altered in brain activity and functional connectivity consistent with accelerated brain maturation, particularly in frontal regions (Myers et al, ; Welch et al, ), lowered symptoms of maternal depression post discharge (Welch et al, ), and improved neurobehavioral outcomes to 18 months of age (Welch et al, ). Given the emphasis of the intervention on dyadic emotional connection and the linkage between autonomic activity, emotion regulation, and social engagement (Porges, ), we hypothesized that with improved emotional connection FNI infants would exhibit signs of a more mature vagal regulation system very early in life (Welch & Ludwig, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FNI was designed to help reestablish the emotional connection (Hane et al, ) between mothers and their infants that was disrupted by the preterm delivery and the experiences of mother and infant within the NICU. Findings thus far have shown that FNI led to greater maternal sensitivity during routine caregiving behavioral interactions (Hane et al, ), altered in brain activity and functional connectivity consistent with accelerated brain maturation, particularly in frontal regions (Myers et al, ; Welch et al, ), lowered symptoms of maternal depression post discharge (Welch et al, ), and improved neurobehavioral outcomes to 18 months of age (Welch et al, ). Given the emphasis of the intervention on dyadic emotional connection and the linkage between autonomic activity, emotion regulation, and social engagement (Porges, ), we hypothesized that with improved emotional connection FNI infants would exhibit signs of a more mature vagal regulation system very early in life (Welch & Ludwig, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The initial randomized clinical trial (RCT), comparing FNI with standard care (SC) demonstrated feasibility and safety of the intervention (Welch et al, ), showed that FNI mothers exhibited increased maternal sensitivity during normal caregiving activities when their infants were approximately 36 weeks postmenstrual age (PMA) (Hane et al, ), and decreased symptoms of anxiety and depression when their infants were 4 months corrected age (Welch et al, ). At ~41 weeks PMA, FNI infants had robustly increased high‐frequency electroencephalogram (EEG) power (Welch et al, ), altered EEG‐based functional connectivity (Myers et al, ), and advanced maturation (Welch et al, ). At 18 months corrected age, FNI infants had improved scores on the Bayley‐III, fewer attention problems on the Child Behavioral Check List, and decreased risk for socio‐emotional problems as assessed by the Modified Checklist for Autism in Toddlers‐Revised (Welch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Results of the trial showed that an average of four facilitated calming sessions per week between mother and infant significantly improved FNI maternal caregiving behaviors at 36 weeks and decreased maternal depressive and anxiety symptoms in infants assessed at 4 months of age (Welch, Halperin et al, 2016). FNI infants showed highly significant increases in EEG power and decreases in EEG coherence at term age in frontal areas associated with socio-emotional outcomes that predict improved outcomes Myers et al, 2015;Welch, Myers et al, 2014). FNI infants also showed significantly improved social relatedness, attention, neurodevelopment, and decreased risk for autism spectrum disorder at 18 months corrected age (Welch et al, 2015).…”
Section: Family Nurture Interventionmentioning
confidence: 99%
“…In a prior report we found that, at term age, FNI infants had decreased EEG functional connectivity (coherence) between the left and right frontal polar regions . These results suggested that at term age FNI infants express greater regional independence of frontal electrocortical activity.…”
Section: Resultsmentioning
confidence: 54%
“…Studies of electroencephalography (EEG) during the period following premature birth show that power, coherence and bursting activity are changing rapidly . However, EEG functional connectivity and brain gyrification in preterm infants at term age are not the same as in infants born full term .…”
Section: Introductionmentioning
confidence: 99%